2018
DOI: 10.1161/jaha.117.007943
|View full text |Cite
|
Sign up to set email alerts
|

Provider Specialty, Anticoagulation Prescription Patterns, and Stroke Risk in Atrial Fibrillation

Abstract: BackgroundDifferences in anticoagulation rates and direct oral anticoagulant use by provider specialty may identify an area of practice improvement to reduce future stroke events in patients with atrial fibrillation (AF).Methods and ResultsWe examined anticoagulant prescription fills in 388 045 (mean age, 68±15 years; 59% male) patients with incident AF from the MarketScan databases between 2009 and 2014. Provider specialty and filled anticoagulant prescriptions around the time of AF diagnosis (3 months before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
3
22
1
Order By: Relevance
“…We also examined whether there was a beneficial association of early cardiology involvement around the time of AF diagnosis among patients who had a history of cancer. In addition to confirming this beneficial association (9,10), we have demonstrated that early cardiology involvement shortly after AF diagnosis is less likely in those who have a history of cancer. Due to the favorable association of cardiology provider involvement on oral anticoagulant prescription fills in AF patients with a history of cancer, early referral to cardiology specialists shortly after diagnosis may be beneficial to increase the use of antithrombotic agents and reduce the risk of future stroke events in this subset of AF patients.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…We also examined whether there was a beneficial association of early cardiology involvement around the time of AF diagnosis among patients who had a history of cancer. In addition to confirming this beneficial association (9,10), we have demonstrated that early cardiology involvement shortly after AF diagnosis is less likely in those who have a history of cancer. Due to the favorable association of cardiology provider involvement on oral anticoagulant prescription fills in AF patients with a history of cancer, early referral to cardiology specialists shortly after diagnosis may be beneficial to increase the use of antithrombotic agents and reduce the risk of future stroke events in this subset of AF patients.…”
Section: Discussionsupporting
confidence: 69%
“…This suggests that greater differences in oral anticoagulant fills will be observed in AF patients with a history of cancer who are younger, and this possibly is related to provider perception of poor survival in younger patients with a history of cancer. Alternatively, cancer history may have limited additive influence in older adults, as they are less likely to see a cardiology provider or fill an anticoagulant prescription regardless of cancer history (10). However, the explanations provided for variation by age are speculative and further research is needed to understand this difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our goals were to determine the prevalence of use of OTC medications and dietary supplements with potentially serious interactions with apixaban, one of the most frequently prescribed DOACs, and to assess patient knowledge of potentially serious OTC product–apixaban interactions.…”
Section: Major Potential Otc Product and Apixaban Interactionsmentioning
confidence: 99%
“…A recent claimed data analysis in the United States evaluated the occurrence of stroke and risk of bleeding among the atrial fibrillation patients with history of cancer. The results found that early cardiology involvement with oral anticoagulant reduced the risk of stroke with an increase of bleeding in patients with either active or remote history of cancer [29].…”
Section: Secondary Prevention For Stroke Patients With Cancer-associamentioning
confidence: 99%